Masculine Ideology and Gender Role Conflict among Pastor’s Husband - Karina Meriem Beru Brahmana (Universitas Ahmad Dahlan, 2019)
AbstractÂ This study aims to measure the correlation between masculine ideology and gender role conflict among the pastor's husband. This study included 40 GBKP pastors' husbands using two measuring scales, namely the male role norm scale compiled by Thompson &Pleck (1986) and the gender role conflict scale compiled by O'Neil et al. (1986). Pearson product-moment correlation coefficient statistics revealed a positive relationship between masculine ideology and gender role conflict, r=0.484 at p<.05. The findings were discussed, and suggestions made.Keywords: Masculine ideology, gender role conflict, pastor